BUCCAL DRUG DELIVERY SYSTEM : HISTORY AND RECENT DEVELOPMENTS - jL, Arun; RANI S; MANOJ KUMAR P (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Abstract Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Of the various routes of drug delivery, the oral route is most ancient as well as preferred by the patient being convenient to take. However, peroral administration of drugs has short comings such as hepatic first-pass metabolism and enzymatic degradation within the GI-tract which comprehend a hindrance to the absorption of peptides and protein group of drug. The drug absorption takesplace faster as it is in contact with the absorption surface. The drug delivery system helps the drug to remain at the same place of application longer for once or twice daily dosing. For some drugs alternate way of administration results in novel methods of action as opposed to the above said procedure. The characteristics of the oral mucosa as well as physicochemical properties of the drug poses as a hindrance to the oral mucosal administration of some drugs. Commercial availability of drug is restricted, although most of the drugs are qualitatively assessed for oral transmucosal delivery. The clinical benefit produced by an oral transmucosal dosage form is good eventhough the production of this dosage form is expensive. Transmucosal products are the recent drug delivery strategies. Delivery through transmucosal benefits the absorption four times than that of skin. Considering the availability of products, only some drugs are used for oral transmucosal delivery. So new drugs have to be processed and developed inorder to meet the limited transmucosal drug delivery. Present paper intends to emphasis the importance of oral transmucosal drug delivery and also highlights on the latest advancement in the field.Â Â